Monoclonal antibodies to Escherichia coli 50S ribosomes. - Shen, V (1980)
Hybridoma cell lines that produce monoclonal antibodies directed against 50S Ribosomal proteins have been isolated. Spleen cells (from BALB/c mice immunized with 50S ribosomal subunits extracted from Escherichia coli) were fused to mouse myeloma cell line SP2/O-Ag 14. The initial screening for antibody producing hybridomas was carried out by a double antibody sandwich method; hybridomas were subsequently cloned in soft agar. Antibodies were characterized by their specific binding to individual 50S ribsomal proteins separated on phosphocellulose columns and in two-dimensional polyacrylamide gels. The assignments were confirmed with purified single ribosomal proteins. Of four clones analyzed thus far, two are identical with specificity for r-protein L5. The other clones produce two different antibodies directed against r-protein L20. Each monoclonal antibody formed ribosome dimers visualizable in the electron microscope. Dimers could be reacted with a different second antibody to form chains containing 8 or more ribosomes, which may be useful for structural studies.